Vitamin D analogs and bone: preclinical and clinical studies with eldecalcitol - Matsumoto, Toshio (Nature Publishing Group, 2014)
Eldecalcitol [1α,25-dihydroxy-2β-(3-hydroxypropyloxy)vitamin D(3)] is an analog of 1α,25-dihydroxyvitamin D(3) [1,25(OH)(2)D(3)], bearing a hydroxypropyloxy residue at the 2β position. In preclinical studies, eldecalcitol suppressed bone resorption to a greater extent than alfacalcidol but had a similar effect on bone formation and Ca metabolism, resulting in a greater increase in bone mineral density (BMD) in ovariectomized (OVX) rats. Histological analysis in OVX rats immediately after ovariectomy revealed that eldecalcitol reduced osteoclast number and bone resorption parameters with a decrease in bone formation parameters. Eldecalcitol also promoted focal bone formation independent of bone resorption, a process known as bone minimodeling. In clinical studies, eldecalcitol showed stronger effects than alfacalcidol in increasing BMD and reducing bone resorption markers in osteoporotic patients under vitamin D supplementation. A 3-year randomized, double-blind, active-comparator clinical trial demonstrated that once-daily 0.75 μg eldecalcitol reduced vertebral fracture incidence by 26% compared with 1.0 μg alfacalcidol. Eldecalcitol also reduced the incidence of wrist fractures by 71% compared with alfacalcidol. Although this may be due to the previously reported effect of vitamin D in reducing the incidence of falls, it is not known whether eldecalcitol has a stronger effect in preventing falls than alfacalcidol. Because eldecalcitol stimulates intestinal Ca absorption and improves Ca balance in addition to its skeletal effects, combination treatment with antiresorptive agents may be able to show better effects than native vitamin D and Ca supplementation in preventing fractures in osteoporotic patients. Further studies are warranted to clarify these issues.